Dinamika Sosial dan Budaya dalam Lagu Yok Miak: Analisis Wacana Kritis Van Dijk - Yuliasari, Yuliasari; Mahliatussikah, Hanik (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
This study is motivated by the limited number of critical studies on regional songs as representations of social and cultural realities within local communities, particularly in Bangka. The popular song “Yok Miak” in this region contains narratives of collective identity, cultural values, and power relations that have yet to be thoroughly examined in academic discourse. Therefore, this research aims to reveal the social representations and cultural dynamics of Bangka society embedded in the song “Yok Miak” by employing Van Dijk’s Critical Discourse Analysis model. This study uses a descriptive qualitative method. The data consists of the song's lyrics, with sources obtained from textual documents, informal interviews with local cultural figures, and observation of the social context in Bangka. Data collection techniques include documentation, participatory observation, and open interviews, while data analysis is based on Van Dijk’s analytical framework covering macrostructure, superstructure, and microstructure. The findings indicate that the song not only conveys local values such as mutual cooperation and social responsibility but also reflects resistance to external cultural influences and efforts to preserve Bangka Malay identity. The song functions as an ideological medium that reinforces collective awareness through discursive strategies that emphasize positive self-representation and the cultural values embedded within the community.